2020
DOI: 10.1002/jbmr.3962
|View full text |Cite
|
Sign up to set email alerts
|

A Single Infusion of Zoledronate in Postmenopausal Women Following Denosumab Discontinuation Results in Partial Conservation of Bone Mass Gains

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 27 publications
2
53
2
1
Order By: Relevance
“…An observational study including 120 postmenopausal women treated with DMAB for 2 to 3 years (81%) were given a single infusion of ZOL 5 mg 6 months after the last DMAB injection. ( 16 ) Six to 36 months after ZOL treatment BMD had decreased significantly by 3.3%, 2.2%, and 1.5%, at the spine, TH, and FN, respectively. CTX and P1NP measured in a subgroup ( n = 27) at the same time point were within the reference range.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…An observational study including 120 postmenopausal women treated with DMAB for 2 to 3 years (81%) were given a single infusion of ZOL 5 mg 6 months after the last DMAB injection. ( 16 ) Six to 36 months after ZOL treatment BMD had decreased significantly by 3.3%, 2.2%, and 1.5%, at the spine, TH, and FN, respectively. CTX and P1NP measured in a subgroup ( n = 27) at the same time point were within the reference range.…”
Section: Discussionmentioning
confidence: 87%
“…Three case series, ( 10,14,15 ) an observational study, ( 16 ) and a clinical trial ( 17 ) have investigated the effect of treatment with ZOL subsequent to DMAB. Horne and colleagues ( 15 ) found that BMD gains obtained during treatment with romosozumab for 1 year and DMAB for 2 years (Fracture Study in Postmenopausal Women with Osteoporosis [FRAME]) were maintained in 73% to 87% of patients 12 months after receiving an infusion of ZOL 8 months (median) after discontinuing DMAB.…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple vertebral fractures have been described in two patients provided with alendronate after treatment with denosumab for an average of 3.5 years . In comparison to oral bisphosphonate treatment, there is conflicting evidence regarding whether zoledronic acid can prevent rebound bone loss associated with denosumab discontinuation, with most data showing this potent antiresorptive agent to be less effective at maintaining BMD when previous denosumab treatment exceeded 2 years compared with a shorter duration of denosumab therapy . Furthermore, there is controversy over the optimal timing and dosing of bisphosphonate therapy after denosumab discontinuation, although ongoing randomized controlled trials are expected to shed more light into this matter.…”
Section: Pharmacologic Osteoporosis Treatmentmentioning
confidence: 99%
“…Regarding the timing of ZOL administration, it has been reported that after Dmab administration over 2 years, ZOL was administered after 191-353 days of the last Dmab administration and BMD obtained with Dmab could be maintained 1 year later [23]. In addition, after Dmab administration over 3 years, ZOL was administered after 6 months of the last Dmab administration, and BMD obtained with Dmab could be maintained 2.5 years later [25]. In our investigation, the transitional period from the last Dmab administration to the start of the ZOL administration was 277.8 days (from 182 to 495 days), according to the patients' convenience, and the timing of ZOL administration may have been delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Sequential therapy with Alendronate (ALN) maintained BMD, if the period of Dmab administration was 1 year [ 22 ]. Sequential therapy with ZOL maintained BMD, if the periods of Dmab administration were 2, 2.2 and 3 years, respectively [ 23 25 ]. However, sequential therapy with ALN reduced BMD, if the period of Dmab administration was 3.5 years [ 26 ].…”
Section: Discussionmentioning
confidence: 99%